Phenolic Alterations in Grape Leaves, Berries and Wines Due to Foliar and Cluster Powdery Mildew Infections - PRAVIN B. TAWARE,; KONDIRAM N. DHUMAL,; DASHARATH P. OULKAR,; SANGRAM H. PATIL,; KAUSHIK BANERJEE, (International Journal of Pharma and Bio Sciences, 2010)
The total phenolics and individual phenolics of the groups; hydroxybenzoic acids, hydroxycinnamic acids, flavonols, flavonol algycones, flavan-3-ols, stilbenes and anthocyanins were analysed from healthy and powdery mildew infected grape leaves, berries and wines. The wine varieties viz., Cabernet Sauvignon and Sauvignon blanc reported higher leaf phenolic content as compared to a table grape variety- Thompson Seedless. Significant increase in total phenolic content of leaves was registered with increase in foliar disease severity. Berries and wines of Cabernet Sauvignon exhibited polynomial pattern of total phenolic content with increase at lower levels of infection followed by decreasing trend. However, Sauvignon blanc wines reported linear negative relationship with powdery mildew infection levels. Phenolic profile of the leaves, berries and wines was significantly altered by the disease. The foliar infection in general resulted into accumulation of phenolic compounds in leaves and reduction in berries and wines due to cluster disease infection. Multifold accumulation of resveratrol was recorded in infected berries and its wines while anthocyanins were reduced significantly due to infections.